The dynamics of governing enterprise blockchain ecosystems - Birgitte van Haaren-van Duijn; Jaime Bonnín Roca; Annie Chen; A. Georges L. Romme; Mathieu Weggeman (Administrative Sciences, 2022)
The aim of this paper is to analyze how the governance of an enterprise blockchain ecosystem changes as it matures and increases in size. A review of the literature serves to identify five behavioral drivers of governance, which appear to affect the long-term viability of a blockchain ecosystem: access rights, decision rights, incentives, accountability, and conflict resolution. We subsequently report the findings from a comparative case study of how three large blockchain ecosystems implemented various governance mechanisms to exploit and modify the five behavioral drivers over time. Based on twenty-six interviews and approximately 200 h of participant observations, we propose an analytical framework that consists of three distinctive stages in the life cycle of a blockchain ecosystem. Each stage is characterized by an intricate relationship between off-chain and on-chain governance mechanisms. Based on these findings, various recommendations are provided to increase the long-term viability of blockchain ecosystems.
Keywords: 350; behavioral drivers; blockchain; case study; consensus mechanisms; dynamics; ecosystems; governance